Construction of a sustainable residential college: the comfort of the residents on the convenience of residential college rooms in public universities - Buyung, Mohd Reduan; Shafii, Haryati (Global Academic Excellence, 2018)
A comfortable residential college is housed in contributing to the quality of life of students. The problem of this study is the discomfort of students when staying in public university residential colleges. As a result of the poor impact on the learning process of the inhabitants further affects the sustainability of residential colleges. This problem eventually leads to the deterioration of the quality of life of the occupants. Therefore, this study was conducted to explore aspects of the provision of accommodation facilities in public university residential colleges. The purpose of this study is to identify the level of comfort of the occupants' room at the public university residence, Quantitative data collection. The study involved seven public university residential colleges from USM, UPM, UTHM, UITM, UTEM, UPSI and UKM (2874 respondents). Descriptive and inferential data analysis is used for quantitative data using Statistical Package for the Social Sciences (SPSS) software. The results showed that the comfort of the respondents on the provision of accommodation was at a comfortable level. T test shows female respondents have higher level of comfort. Comfort in staying in a residential college is important as it is able to impact the overall quality of life of the occupants. As a result of this assessment, it is possible to find the current situation of the occupants of the existing accommodation facilities that will be used to develop a sustainable residential college and be more conducive and conducive in the future.